The Authority of The Regional Supervisory Council for Notaries in Enforcing The Notarial Code of Ethics - Myaskur, Myaskur; Wahyudiono, Tri (UNISKA LAW REVIEW, 2025)
This study aims to analyze and formulate the ideal model of authority of the Regional Supervisory Council of Notaries in enforcing the Notary Code of Ethics to ensure that the supervision of the notarial profession operates effectively, independently, expeditiously, and accountably. This legal research adopts a statute approach, a conceptual approach, and a comparative approach. The findings reveal that the authority of the Regional Supervisory Council of Notaries is administrative in nature and limited to overseeing the exercise of public office, whereas the enforcement of the Code of Ethics falls under the jurisdiction of the Notary Honorary Council as a professional organizational body. The ambiguity in delineating these authorities has led to overlaps and inefficiencies in the process of enforcing professional discipline. Consequently, this study proposes an integrated supervisory authority model that affirms the synergy between the Regional Supervisory Council and the Notary Honorary Council through a coordinated mechanism without overlapping functions or powers. The novelty of this research lies in the formulation of an integrated supervision concept grounded in the general principles of good governance, combining elements of positive law, professional ethics, and public accountability as the normative foundation for upholding notarial ethics within the framework of a democratic and religious rule of law state.